Fabrication of CdS/β-SiC/TiO2 tri-composites that exploit hole- and electron-transfer processes for photocatalytic hydrogen production under visible light. (25th January 2018) - Nagakawa, Haruki; Ochiai, Tsuyoshi; Nagata, Morio
Abstract: In this work, CdS/SiC/TiO2 tri-composite photocatalysts that exploit electron- and hole-transfer processes were fabricated using an easy two-step method in the liquid phase. The photocatalyst with a 1:1:1 M ratio of CdS/SiC/TiO2 exhibited a rate of hydrogen evolution from an aqueous solution of sodium sulfite and sodium sulfide under visible light of 137 μmol h −1 g −1, which is 9.5 times that of pure CdS. β-SiC can act as a sink for the photogenerated holes because the valence band level of β-SiC is higher than the corresponding bands in CdS and TiO2 . In addition, the level of the conduction band of TiO2 is lower than those of CdS and β-SiC, so TiO2 can act as the acceptor of the photogenerated electrons. Our results demonstrate that hole transfer and absorption in the visible light region lead to an effective hydrogen-production scheme. Highlights: A rate of hydrogen evolution of β-CdS/SiC/TiO2 is 9.5 times of pure CdS. Hydrogen production by β-CdS/SiC/TiO2 can proceed under visible light. Hole-transfer mechanism leads to an effective hydrogen-production scheme. CdS covered by β-SiC and TiO2 has a benefit to suppress its photo-corrosion.